CMT585: Petroleum Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2021)
The course covers description of the chemical compositions and physical properties of petroleum, petroleum drilling, completions and production, reservoir mechanics, fundamentals of rock and fluid properties, petroleum products, natural gas and petrochemical feedstocks. This includes methods for fractionation and analysis both oil-well and pipeline quality, the chemical basis of the central refinery processes and an overview of the spectrum of products from oil refining. Additional subjects include natural gas processing from well to plant and petrochemical processing and economics.